An Overview and Management of Painful Menstrual Disorder (Dysmenorrhea): A Narrative Literature Review - Juntu, Petrus; Gede Ananta (Sriwijaya Journal of Obstetrics and Gynecology, 2023)
Primary dysmenorrhea is menstrual pain associated with the release of prostaglandins in the ovulatory cycle, but not with the pelvic disease. Approximately 90% of all women experience dysmenorrhea, 15% of whom are unable to last 1 to 3 days because of the severity of the pain. This literature review aimed to describe an overview and management of dysmenorrhea. Primary dysmenorrhea usually begins with the onset of ovulation cycles, with the highest prevalence in adolescence. In contrast, secondary dysmenorrhea is associated with pelvic pathology (i.e., ovarian cysts, adenomyosis, endometriosis) that manifests in later reproductive years and can occur at any point in the menstrual cycle. Administration of nonsteroidal anti-inflammatory drugs (NSAIDs) is the treatment of choice because these drugs reduce the activity of the cyclooxygenase (COX) enzyme and, thus, the production of prostaglandins. NSAIDs work in the majority of women with primary dysmenorrhea and are most effective when started at the first sign of bleeding or cramping.